Taichi-LBM3D: a single phase and multiphase lattice Boltzmann solver on cross-platform multi-core CPU/GPUs - Yang, Jianhui; Xu, Yi; Yang, Liang (MDPI, 2022)
The success of the lattice Boltzmann method requires efficient parallel programming and computing power. Here, we present a new lattice Boltzmann solver implemented in Taichi programming language, named Taichi-LBM3D. It can be employed on cross-platform shared-memory many-core CPUs or massively parallel GPUs (OpenGL and CUDA). Taichi-LBM3D includes the single- and two-phase porous medium flow simulation with a D3Q19 lattice model, Multi-Relaxation-Time (MRT) collision scheme and sparse data storage. It is open source, intuitive to understand, and easily extensible for scientists and researchers.
Keywords: GPU computing; lattice Boltzmann; two-phase flow; capillary pressure; Taichi programming